Acute myocardial infarction associated with high dose intravenous immunoglobulin infusion for autoimmune disorders. A study of four cases. Issue 1 (1st January 2000) - Elkayam, Ori; Paran, Daphna; Milo, Ronny; Davidovitz, Yaron; Almoznino-Sarafian, Dorit; Zeltser, David; Yaron, Michael; Caspi, Dan
Abstract : OBJECTIVE: To report on four patients with autoimmune disorders who developed acute myocardial infarction (MI) during or soon after treatment with high dose intravenous immunoglobulins (IVIG) and to determine the clinical profile of patients prone to this complication. METHODS: The clinical history of the four patients is reported with details concerning age, sex, indication for IVIG treatment, risk factors, timing of the MI and outcome. The relevant medical literature has been reviewed. RESULTS: The patients, three men and one woman, aged 42–67, received IVIG treatment for different autoimmune disorders. All had a history of atherosclerosis or previous risk factors such as hypertension, stroke, hyperlipidaemia and obesity. Two of the patients suffered a MI after the first infusion of IVIG while the others—after the 5th and 15th pulses. MI occurred during the infusion in two patients and after a few days in the others. All the patients recovered from the acute event. These observations are in concert with sporadic cases of IVIG related thrombosis reported in the medical literature. CONCLUSION: In patients with vascular risk factors such as old age, hypertension, history of stroke or coronary artery disease, the possibility of IVIG related vascular complications should be considered and IVIG prescribed with a cautious reweighted risk/benefit consideration.